PENILAIAN KESESUAIAN ANTARA PROGRAM PERLINDUNGAN DATA DARI KANTOR PUSAT DENGAN PERATURAN PERLINDUNGAN DATA YANG BERLAKU DI INDONESIA - Fritz Gamaliel; P. Yudi Dwi Arliyanto (Jurnal Manajamen Informatika Jayakarta, 2025)
To ensure information security, the head office has issued a data protection program to be implemented by its branch offices. Branch offices have a policy to assess the head office program based on the regulations applicable in Indonesia. Therefore, the objective of this study is to evaluate the correlation between the head office’ data protection program and the data protection regulations applicable in Indonesia. This study adopts an approach focused on reviewing relevant literature to support the research objectives. The study findings indicate that there are several aspects of the data protection program from the head office that are not yet fully aligned with the data protection regulations applicable in Indonesia.